Healthcare transition in patients with rare genetic disorders with and without developmental disability: Neurofibromatosis 1 and williams–beuren syndrome. Issue 7 (21st May 2013) - Van Lierde, Andrea; Menni, Francesca; Bedeschi, Maria Francesca; Natacci, Federica; Guez, Sophie; Vizziello, Paola; Costantino, Maria Antonella; Lalatta, Faustina; Esposito, Susanna
Abstract There are between 5, 000 and 8, 000 distinct rare diseases (RDs) affecting 6–8% of the population, most of which are caused by genetic defects. Many are highly complex, childhood‐onset, multi‐system disorders that are often associated with developmental disability, and require lifelong, highly specialized care and support. As larger numbers of children with previously fatal RDs survive into adulthood, they encounter significant challenges in transitioning from family‐centered, developmentally focused, multidisciplinary pediatric care to a less supportive adult healthcare system that is often unfamiliar with these conditions. This paper discusses the challenges of the transition from pediatric to adult health care in two groups of patients with multisystem genetic RDs (neurofibromatosis 1 [NF1] and Williams–Beuren syndrome [WBS]), and analyzes strategies for making the process easier for patients with and without developmental disabilities. Our findings show that there are still no guidelines in national healthcare programs on how to transition RD adolescents with and without developmental disabilities, and only a few pediatric centers have implemented the elements of transition in their general practice. Evidence regarding programs to facilitate transition is inconclusive and the transition from pediatric medicine to adult medicine for RDs remains a major challenge. However, transition requires both time and personnel, which are difficult to find in periods of fiscal austerity. Nevertheless, we should strongly advocate for governments investing more into transition infrastructure or they will face increased long‐term social and economic costs due to poor treatment compliance, disengagement from services, increased genetic risks, and higher rates of disease‐related complications. © 2013 Wiley Periodicals, Inc.